2006
DOI: 10.1002/pssb.200671516
|View full text |Cite
|
Sign up to set email alerts
|

Dephasing of excited‐state excitons in InGaAs quantum dots

Abstract: We measure the dephasing time of the first optically-active excited-state excitonic transition in strongly confined InGaAs quantum dots using transient four-wave mixing. The optically-driven excited-state polarization shows a bi-exponential decay with a significant fraction of the probed excited states exhibiting a very long dephasing time, in the nanosecond range at 10 K. The full time-dependent four-wave mixing polarization is microscopically calculated by taking into account both virtual and real acoustic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…4 (d) could be significantly less affected by acoustic phonon scattering, allowing excitons to dephase at their zero-phonon dephasing rate or both levels are affected similarly and quantum oscillations between both dephasing components in two different levels sharing the same ground state are observed. The inhomogeneous broadening would damp the beating amplitude depending on the degree of correlation 30,31 . Coherent LO phonons can certainly generate oscillation when the time delay T is scanned which can affect the dephasing rate τ according to the oscillation period along T, but should not generate beating in τ 14 .…”
Section: Resultsmentioning
confidence: 99%
“…4 (d) could be significantly less affected by acoustic phonon scattering, allowing excitons to dephase at their zero-phonon dephasing rate or both levels are affected similarly and quantum oscillations between both dephasing components in two different levels sharing the same ground state are observed. The inhomogeneous broadening would damp the beating amplitude depending on the degree of correlation 30,31 . Coherent LO phonons can certainly generate oscillation when the time delay T is scanned which can affect the dephasing rate τ according to the oscillation period along T, but should not generate beating in τ 14 .…”
Section: Resultsmentioning
confidence: 99%
“…This picture is valid at very low temperatures. In an ordinary vacuum, this corresponds to the situation where the dynamics of quantum dots and their polarization decay is "radiatively limited" [29,32,33]. In a PBG material, where radiative processes can be suspended on timescales much longer than in ordinary vacuum, it is important to consider additional channels for phonon-mediated decay of the photon-atom bound state.…”
Section: A Undamped Acoustic Phononsmentioning
confidence: 99%
“…Experimental studies [29][30][31] in strongly confined quantum dots at low temperatures have clearly demonstrated that the polarization decay has a non-Lorentzian homogenous line shape with a very narrow zero-phonon line superimposed on a broad acoustic-phonon spectrum. These In x Ga x−1 As/GaAs quantum dot excitons have lifetimes as long as T 1 = 900 ps in an unstructured electromagnetic vacuum with dephasing times T 2 = 630 ps at cryogenic temperatures [32][33][34]. Since the dephasing times are almost as large as the decay times, dephasing in these materials is radiatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…In these InGaAs/GaAs quantum dots, exciton lifetimes in free space were measured to be as long as T 1 ¼ 900 ps with dephasing times T 2 ¼ 630 ps. In In 0.6 Ga 0.4 As/GaAs self-assembled quantum dots the dephasing times were measured to be as long as the decay times [24][25][26][27][28][29]. The exciton lifetime can be further extended by placing these quantum dots inside the structured reservoir of the photonic crystal, as a radiative recombination of the electrons and the holes is suppressed if the energy of the emitted photon is deep inside the photonic band gap.…”
Section: Introductionmentioning
confidence: 99%